INTELLECTUAL CAPITAL FRAMEWORK PERGURUAN TINGGI DI INDONESIA BERDASARKAN INSTRUMEN AKREDITASI PROGRAM STUDI (IAPS) 4.0 - Ulum, Ihyaul (Universitas Muhammadiyah Malang)
This study aims to construct the intellectual capital framework (ICF) of universities in Indonesia based on the Study Program Accreditation Instrument (IAPS) 4.0. Using an exploratory approach, this research was conducted through a focus group discussion (FGD). The FGD was conducted with researchers in the field of intellectual capital (IC) and a number of assessors of the National Accreditation Board for Higher Education (BAN PT) who understood the process of changing from 7 standards to 9 criteria (IAPS 4.0). This study resulted in a university ICF consisting of 60 items: 30 items of human capital components, 18 items of structural capital components, and 12 items of relational capital components. In addition, this study also suggests the use of six ways of numerical coding system in conducting content analysis of this framework.